SKIN AS A PAIN RECEPTOR: - M Royyan Nafis FW (Dirosatuna: Journal of Islamic Studies, 2019)
This research is motivated by the problem of the continued development of science and technology. This means that the interpretation of the Qur'an which is stagnant must continue because it is given the dynamic Koran. Recently discovered that the brain does not act as a pain receptor felt by the body but the skin. Surprisingly, this was explained by the Koran long before the discovery of that discovery. In the Koran an-Nisa 'verse 56 explained that the time will come when people who reject the religion of God will be put into hell and tortured in the form of skin changes. when evidenced by the very combustion process, the sensory nerve endings will be damaged. This results in the skin no longer being able to receive stimulation. Therefore, in hell God replaces the skin of the inhabitants of hell with a new skin which is intended to renew sensory nerve endings so that they feel the torments of hell again. The purpose of this study is to harmonize by presenting scientific evidence as a means of supporting interpretation. This study uses a qualitative research model which in its presentation uses descriptive-analysis techniques. This research is based on the scientific interpretation theory. Data collection was carried out using library research techniques in the form of interpretation books, science books and books that have a correlation with this research. The results of this study are the findings of science have been written in the Koran. Basically when the skin is burned, there will be three phases of change in the skin, namely first bruising, then feeling severe pain, and finally numbness because the sensory nerve endings in the skin have been damaged.